PENGARUH GAME ONLINE HIGGS DOMINO ISLAND TERHADAP KETAHANAN KELUARGA DI NAGARI PASIE LAWEH MENURUT PERSPEKTIF HUKUM ISLAM - Atika Fadhila; Elsy Renie (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
This study examines the views of Islamic law regarding the influence of the higgs domino island online game on family resilience in Nagari Pasie Laweh. The problem is the phenomenon that is happening right now is the rise of online game play, such as the online game higgs domino island where this game is not only for children, teenagers, even married men who are also playing this game. From these problems, the question arises how the influence of the higgs domino island online game has on family resilience in Nagari Pasie Laweh, what is the view of Islamic law regarding the influence of the higgs domino island online game on family resilience. This research is a field research. Data obtained through interviews, documentation. After the collected data was processed qualitatively, it was analyzed by means of data reduction, data presentation, and conclusions. Furthermore, the data is narrated descriptively. This study found, first, the effect of the higgs domino island online game on family resilience, the economic aspect of the husband is negligent with the obligation to provide a living, the husband is physically unable to fulfill family nutrition, the husband's religion rarely performs worship, rarely invites children and wife to worship, psychologically disturbed, easily anger, social reduced family interaction with the surrounding community. The two analyzes of Islamic law are related to the influence of the higgs domino island online game on family resilience, indeed the game has stakes, and is categorized as maisir but when viewed from Saad al Dzari'ah's study regarding family resilience that it causes more mafsadah (damage) than benefits. Because it is very contrary to a provision of the rights and obligations of husband and wife that have been determined by fiqh. Resulting in husbands/wives neglecting to exercise their rights, therefore of course it is totally against Islamic law, prevented by closing with this study.